(untitled) (Research, Society and Development, 2022)
Introduction: The climacteric is a natural cycle of life that is of great importance in a woman’s life, because during this period the woman undergoes several physical, biological, psychological and social changes due to the progressive decrease in hormones produced. Objective: to analyze the importance of food potential in the climacteric period for women’s quality of life. Methodology: The present study is bibliographic research. Results: The study of dietary patterns in menopausal women is important because this is a relatively long period in a woman’s life and the diet adopted has a great impact on public health. Develop nutritional education guidelines and interventions aimed at promoting measures to alleviate the problems of this period. Conclusion: the nutritionist’s role in the care of women is in line with other studies that professionals need to rethink nursing practice, with other health professionals clarifying the implementation of Measures focused on women in menopause, meeting their needs and guiding them. them to lead an active, healthy, productive life, with well-being and quality.